AN EMPIRICAL STUDY ON AGRICULTURAL FINANCE PROVIDED BY COMMERCIAL BANKS TO THE AGRICULTURAL SECTOR IN VILLUPURAM DISTRICT, TAMIL NADU - J. KOSALRAM,; C. VENKATESH, (The Bioscan, 2026)
Agricultural finance plays a crucial role in promoting agricultural productivity and rural development by enabling farmers to access essential inputs and modern technologies. The present study examines the extent and pattern of agricultural finance provided by commercial banks and evaluates its utilization, repayment behaviour, and farmers’ satisfaction in Villupuram District, Tamil Nadu. The study is based on primary data collected from 200 farmers through structured questionnaires and supported by secondary data from institutional reports. Descriptive statistics and econometric techniques such as multiple linear regression, logistic regression, and ordered logit models were employed for analysis. The findings reveal that 48% of the respondents are small farmers owning less than two acres of land, and 36% of farmers received agricultural loans ranging between ₹50,000 and ₹1,00,000. The regression results show that loan amount (β = 0.421, p < 0.01), farm size (β = 0.316, p < 0.01), and education level (β = 0.233, p < 0.01) positively influence loan utilization, while interest rate has a negative effect (β = -0.142, p < 0.05). Logistic regression indicates that loan amount (β = 0.563, p < 0.01) and farmer income (β = 0.486, p < 0.01) significantly improve repayment behaviour. Ordered logit results further show that loan amount positively affects farmers’ satisfaction (β = 0.362, p < 0.01), whereas interest rate negatively influences satisfaction (β = - 0.294, p < 0.01). Overall, the study confirms that institutional agricultural finance significantly enhances credit utilization and repayment capacity among farmers.